Fast transient simulation of IEEE recommended surge arrester model on a transmission line using alternative transient program (ATP) - Abu Bakar, Hizal (2015)
This study presents the outcomes of the performance evaluation simulation residual voltage output resulting from lightning arrestors IEEE Recommended model. This simulation uses software Alternative Transient Program - Electromagnetic transients Programmed (ATP-EMTP). This software is very appropriate in examining the behavior of the system, especially a high voltage system lines. As a result of the comparison can be made in the system of 132kV transmission line between systems that are not supplied with lightning arrestors, system supplied with lightning arrestors with conventional styles and systems supplied with lightning arrestors IEEE Recommended model. The results of the simulation study comparisons can be made by taking into account the peak voltage at sub transient conditions. This situation can determine the 132kV transmission line system can protect the equipment properly. Selection lightning 10kA with the 8μs fast front surge and trailing the current time is 20μs is appropriate in the circumstances lightning eruption in Malaysia. In this research, 132kV transmission line parameter tower need to be enclosed by the actual value of the output to the accurate or almost accurate in determining the ability of a lightning arrester in the system.